The Role of Taxpayer Awareness as an Intervening Variable on the Effect of Service Quality with Land and Building Taxpayer Compliance - Rahadhini, Marjam Desma; Sarwono, Aris Eddy (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This researchaims to analyze the effect of service quality on the compliance of Rural and Urban Land and Building Taxpayers (PBB-P2) and analyze the role of the moderating variable of taxpayer awareness as a moderating variable on the effect of service quality variables with PBB-P2 taxpayer compliance. The population of this research is taxpayers in Ponorogo Regency, while the sampling technique uses side purposive randomness. The analysis technique uses regression analysis and path analysis (Part Analysis). The test results show that there is an influence between service quality on compliance with Rural and Urban Land and Building Taxpayers (PBB-P2).